Coronary Thrombosis Case in Female Patient with COVID-19 Confirmed Case: Coincidence or Complication? - Yosua Hendriko Manurung; Yusuf Galenta (Universitas Airlangga, 2022)
The worldwide health impact of the COVID-19 epidemic has been felt all across the world, mostly due to respiratory issues, but many additional signs such as cardiac manifestations and different thromboembolisms have also been observed. Case Summary. We provide you with a 48-year-old female patient with COVID-19 pneumonia following a severe infection, who developed Unstable Angina due to coronary thrombosis. She has a history of hypertension and obese posture. No diabetes, hypercholesterolemia, or smoking habit had been recorded. And she still has regular menstrual cycle. Around a month prior to being referred to our hospital, this patient has been admitted to ICU of satellite hospital. She was treated with ventilator and discharged around a week before she was admitted to our Emergency Department. She had typical chest pain with ST-segment depression ECG at antero-septal area. PCI was performed and a large thrombosis was found at LAD artery. Discussion: Many studies have showed that COVID-19, through various ways, has developed thromboembolism both in arteries and venous system. The actual process of thrombus development in the coronary arteries is unknown, however, it is thought that pro-inflammatory cytokinesis released by the body, which stimulates the coagulation cascade and prevent fibrinolysis, are the major cause. This condition that leads to hypercoagulable state which eventually makes an increased risk of thromboembolism.